Japan’s China policy : a relational power analysis (2017)
Japan has been the subject of many studies in the field of economics and business since the country’s economy took off after World War II. Its remarkable progress in the three decades after 1960 turned it into an economic role model and Japanese management and production techniques were taught at most business schools in the world. When the Japanese economy started slowing down in the 1990s, many of the studies turned to explaining what was wrong with the Japanese economy. Despite the slowdown, however, the sheer size of the Japanese economy has resulted in the portrayal of the country as an ‘economic giant’. In stark contrast, in the field of politics, Japan has always been characterized as a ‘political dwarf’. Despite being one of the biggest contributors to the United Nations and the biggest donor of foreign aid all through the 1990s, Japan was not considered to have any political clout. If it influenced world development at all, it was only through its economic might. Unfortunately, most of the studies undertaken on Japan’s international political behavior have not presented a nuanced view but rather reinforced existant stereotypes, as many of the traditional theories have failed to explain the country’s behavior in international politics.